Menguji dampak laba bersih dan perubahan persediaan dalam memprediksi arus kas operasi d? masa mendatang - Nikke Yusnita Mahardini; Neneng Sri Suprihatin; Yuni Alfiah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2020)
Purpose: This research is an empirical study that aims to empirically examine the effect of net income and inventory changes both partially and simultaneously in predicting future operating cash flows in the food and beverage service sector in 2016-2018. Research methodology: The design in this research was a causality study using the financial statements of service companies in the food and beverage sub-sector in 2016-2018. The number of samples in this study were 33 food and beverage companies selected using the purposive sampling method. The analysis technique used in this study was multiple linear regression. Results: The analysis shows that net income has an effect on predicting future operating cash flows, while changes in inventory have no effect on predicting future operating cash flows. Simultaneous testing was also carried out with the results that net income and changes in inventory affect the operating cash flow in the future. Limitations: This study only focused on using 1 (one) sub sector, which is a company that consumes food and beverages. For further research, it is recommended to use all sub-sectors so that the results can be generalized. Contribution: This study can be used as information material for the accounting profession as to how great the influence between net income and inventory changes in predicting future operating cash flows that can be used in decision making. Also, it can provide information for economic actors or investors about the importance of knowing the company's operating cash flow in the future, so that it can be taken as a consideration in investing. Keywords: Future operating cash flows, Net profit, Changes in inventory